(untitled) (Journal of actual problems of jurisprudence, 2019)
According to the goal of scientific work carried out the identification of problems of legal regulation of customs procedures in the Customs Union. During the study, familiarized with the legal framework of the Customs Union and the analysis of changes in connection with the adoption of the Customs Code of the Customs Union. The analysis considered the advantages and disadvantages of changes of the Customs Code of the Customs Union. Key words: the Customs procedure, the Customs Union, the Customs Code of the Customs Union, Commission of the Customs Union.